Про ще одну концепцію «неоліту» із рисами постмодернізму - Гаскевич, Д.Л. (Археологія, 2022)
У статті проаналізовано теоретичні погляди
В. О. Манька щодо терміна «неоліт» та суті процесу неолітизації. Зроблено висновок, що одні з них
повторюють ідеї представників постпроцесуалістської археології, а решта є, хоч і оригінальними,
проте методологічно неоформленими, сповненими
протиріч та логічних хиб. Valerii Manko and Guram Chkhatarashvili published their article in the “Arheologia”, No. 2, 2022. In the paper, they discussed
the migration of bearers of four Neolithic flint industries from Southwest Asia through the Caucasus to the south of Eastern
Europe from the final Pleistocene to the early Atlantic. According to the authors, stable connections between these remote areas
led to the emergence of four “information networks”, which they called “Cultural-Historical Regions” (CHR). The authors
believe that the first region of such type in human history was the Pre-Pottery Neolithic A (PPNA) in the Near East. Therefore,
they call the “theoretical basis” of their study “the idea of understanding the Neolithic as an epoch of the formation of global
information networks, within which innovations created in the Near and Middle East were disseminated.”
V. Manko began to develop the described theoretical views in 2010 when he wrote that the reason for the emergence of the
CHR is the ability to communicate, formed due to the mental changes of inhabitants of the PPNA large settlements. The statement
about specific psyche and worldview as the basis of Neolithic has been expressed as an idea of Post-Processual archaeology long
before V. Manko announced it. In particular, Trevor Watkins developed this concept in detail. However, V. Manko does not
mention works by any post-processualists in his publications.
The statement about the formation of the ability to communicate only in the Neolithic is V. Manko’s novelty. He based it on
one reference to a publication of Alexey N. Sorokin, who allegedly claimed that the bearers of different flint industries did not
contact each other in the central part of European Russia in the Mesolithic. V. Manko misinterpreted this particular subjective
observation and gave it the meaning of a global pattern. Thus, his definition of the Neolithic is controversial, because of using this
erroneous premise. Generally, V. Manko’s theoretical reasoning is full of contradictions, logical errors, terminological chaos,
and rhetoric in the postmodernism style. It is noteworthy that V. Manko himself does not fully adhere to his previous theoretical
views in his later works.